Spotlight on the Binding Affinity of Ion Channels for Phosphoinositides: From the Study of Sperm Flagellum - Kawai, Takafumi; Okamura, Yasushi (Frontiers in Physiology, 2022)
The previous studies revealed that many types of ion channels have sensitivity to PtdIns(4,5)P2, which has been mainly shown using heterologous expression system. On the other hand, there remains still few evidences showing that PtdIns(4,5)P2 natively regulate the ion channel activities in physiological context. Our group recently discovered that sperm specific K+ channel, Slo3, is natively regulated by PtdIns(4,5)P2 in sperm flagellum. Very interestingly, principal piece, to which Slo3 specifically localized, had extremely low density of PtdIns(4,5)P2 compared to the regular cell plasma membrane. Furthermore, the previous and our studies also revealed that Slo3 had much stronger PtdIns(4,5)P2 affinity than KCNQ2/3 channels which are widely regulated by endogenous PtdIns(4,5)P2 in neurons. Thus, the high-PtdIns(4,5)P2 affinity of Slo3 is well adapted to the specialized PtdIns(4,5)P2 environment in the principal piece. This study sheds light on the relationship between PtdIns(4,5)P2-affinity of ion channels and their PtdIns(4,5)P2 environment in native cells. We discuss the current understanding about PtdIns(4,5)P2 affinity of diverse ion channels and their possible regulatory mechanism in native cellular environment.